Application of ethnobotanical indices for ethnopharmacology and ethnobotany of the family Lamiaceae used by population in National Talassemtane Park (North of Morocco) - Redouan, Fatima Zahrae Zahrae; Cheikh, Yebouk; Crisafulli, Alessandro; Picone, Rosa Maria; Boutahar, Aboubakr; Gargiulo, Gaetano Maurizio; Merzouki, Abderrahmane (Ethnobotany Research and Applications, 2023)
Background: The Talassemtane National Park (PNTLs) characterized by a rich floristic diversity. We carried out an ethnobotanical survey in the PNTLs, we have identified a total of 152 medicinal plant species belonging to 44 botanical families. The Lamiaceae is one of the 20 largest plant families, and one with the significantly higher proportion of medicinal plants. The study aimed to specify the medicinal uses of the Lamiaceae in PNTLs and evaluate the context of the application of ethnobotanical indices. Methods: Open-ended interviews, semi-structured interviews, and questionnaires were conducted between 2014 and 2017 in PNTLs on a sample of 200 people between the ages of 20 and 60. The ethnobotanical data were quantitatively analyzed using indices, Use Value (UV), the Medicinal Plant Knowledge index (MPKi), the Medicinal Plant Use index (MPUi), and the Confidence level (Cl), Informant agreement ratio (IAR). Results: The study identified a total of 27 taxa belonging to the Lamiaceae families. With a total of 3113 use reports, we have identified 183 medicinal uses to treat 58 conditions or symptoms according to the international classification of primary care (ICPC-2). Most remedies are prepared as an infusion (46%), the most used parts of the plant are leaves (34%), and the most common mode of administration is oral (67%). The analysis revealed that the highest value of UV was obtained for Lavandula angustifolia Mill. (UV=1,8). In addition, the highest degree of agreement from informants (IAR) was recorded for Ear disorders (H) and Pregnancy, Childbearing, and Family Planning (W) (1). Conclusions: This study shows a promising perspective for future ethnomedicinal studies, and for the conservation of traditional knowledge of medicinal plants in the Park. Keywords: ethnobotanical indices; medicinal plants; Lamiaceae; Parc National Talassemntane.